1992
DOI: 10.1007/bf01332145
|View full text |Cite
|
Sign up to set email alerts
|

Strategic transfer: A tool for academic problem solving

Abstract: Withh~ the context of classroom learning, strategic transfer can be viewed as a tool for academic problem solving. Strategic transfer is defined as the spontaneous access and retrieval (remembering) of previously learned formal procedures for the successful solution of a problem. The transfer-appropriate processing encoding model (Morris, Bransford, and Franks, 1977), and the transfer-appropriate procedures retrieval model (Roediger, Weldon, and Challis, 1989) are reviewed. An integration of the two models is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 57 publications
1
30
0
2
Order By: Relevance
“…This may overload the working memory and consequently reduce mental efficiency in conducting OOA-to-OOLD transition tasks. This result is consistent with that of previous studies, which indicated that precise elaborations can facilitate efficient schema acquisition and automation in comprehending, learning, and remembering materials [15], [28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may overload the working memory and consequently reduce mental efficiency in conducting OOA-to-OOLD transition tasks. This result is consistent with that of previous studies, which indicated that precise elaborations can facilitate efficient schema acquisition and automation in comprehending, learning, and remembering materials [15], [28].…”
Section: Discussionsupporting
confidence: 93%
“…Inferential reconstruction refers to the process of inferring what is plausible with regard to the schema [27]. Therefore, precise elaborations promote efficient schema acquisition and automation and assist learners in efficiently understanding, memorizing, and recalling material [15], [28].…”
Section: Propositionmentioning
confidence: 99%
“…First, from a functional perspective, human knowledge can be classified into three types. The first type of knowledge is declarative knowledge, including knowing facts, concepts, and so on; the second type is procedural knowledge involving knowing how to use cognitive tools to process declarative knowledge; and the third type is strategic knowledge relating to knowing when and how to use both declarative knowledge and procedural knowledge to solve new learning problems (Phye, 1992, 1996). Skill development in radical knowledge application involves all three of these types of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…and those employees who have or are able to acquire transferable skills and who demonstrate flexible attitudes are likely to be the ones who succeed in a dynamic work environment (Ford & Kraiger, 1995;Hesketh, 1996;Hesketh & Bochner, 1993). Phye (1991Phye ( , 1992 has drawn attention to the way in which an adaptable workforce could make strategic use of metacognitive skills associated with transfer, such as seeking out multiple examples, learning principles. and increasing the accuracy of self-assessment in managing their own careers.…”
Section: Introductionmentioning
confidence: 99%